Extrinsic rewards in family businesses: Perspectives of nonfamily employees - S. M. Farrington; E. Venter; G. D. Sharp (South African Journal of Business Management, 2014)
The rewards employees receive in exchange for their labour play an important role in influencing their levels of job satisfaction and organisational commitment, and ultimately in retaining their services. The Issues surrounding rewards are, however, complex in the field of family business. The primary objective of this paper is to investigate the influence of selected extrinsic rewards, namely, compensation, promotion opportunities and job security, on the levels of jobsatisfaction and ultimately on the levels of organisational commitment of nonfamily employees working in family businesses. Structural equation modelling was used to assess the hypothesised relationships, and the results show that compensation and job security are significantly and positively related to job satisfaction. Job satisfaction was found to be significantly and positively related to organisational commitment and also found to act as a mediator between these extrinsic rewards and organisational commitment. Establishing the perspectives that nonfamily employees have of the rewards given to them by the family businesses in which they work, provides family business owners with valuable insights into attracting and retaining this valuable stakeholder group.
Keywords: 650